Effectiveness of Using Micro Learning Through Web 2.0 Tools in Developing Skills of Multimedia Designing and Production Among 12th Grade Students in Palestine - Abu Sarah, Abdelrahman Mohammad Sadeq (Journal of Educational and Psychological Sciences, 2021)
This research aimed to investigate effectiveness of using micro learning through Web 2.0 tools in developing skills of multimedia designing and production among 12th grade students in Palestine. The study used a one-group pretest-posttest experimental design, while the research sample consisted of (11) second secondary grade students / technology stream in one of Qabatia Directorate of Education schools, in the academic year 2020/2021. A practical performance measurement and a note card were also prepared. After Applying procedures and tools of the research, the results showed a statistically significant difference between the two average degrees of the pretest and the posttest, in favor of the posttest with great influence. In addition, using micro learning through Web 2.0 tools achieved effectiveness (according to Black equation) in developing students’ skills of multimedia designing and production. In light of these results, the researcher suggested a number of recommendations, including: Employing micro learning through Web 2.0 tools in information technology and applied sciences in general, and programming and automation in particular; training teachers and educational supervisors on micro learning content design through digital applications in order to develop different skills among students.